2019
DOI: 10.1002/cite.201800188
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of Reversible Solid Oxide Cells

Abstract: Reversible solid oxide cells (rSOCs) are highly efficient devices, which allow either the generation of electric power or the storage of energy via fuel production. In this paper, the characteristics of the mode switch are investigated by applying a dynamic 3D stack model. The responses of temperature, current density, and species mole fractions regarding a switch from storage (SOEC) to generation mode (SOFC) are examined in detail. Additionally, the impact of using excess air and continuous voltage variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The kinetic model was calibrated with i-V curves of an anodesupported single cell (Ni/YSZ-YSZ-LSM /YSZ) measured by Ebbesen et al [39] at operating temperatures of 1023.15 K and 1123.15 K with various fuel mixtures (H 2 /CO/CO 2 /H 2 O/Ar) in our previous paper [40]. The calibrated kinetic model was then used in stack simulations.…”
Section: Sofc Modelmentioning
confidence: 99%
“…The kinetic model was calibrated with i-V curves of an anodesupported single cell (Ni/YSZ-YSZ-LSM /YSZ) measured by Ebbesen et al [39] at operating temperatures of 1023.15 K and 1123.15 K with various fuel mixtures (H 2 /CO/CO 2 /H 2 O/Ar) in our previous paper [40]. The calibrated kinetic model was then used in stack simulations.…”
Section: Sofc Modelmentioning
confidence: 99%
“…The integrated multiscale model framework has been described in detail in my group's previous publications [3][4][5][6][7][8][9] and is only summarized here. In essence, the framework comprises of individual sub-models that provide continuum descriptions of the relevant physico-chemical phenomena at the multiple time and length scales involved.…”
Section: Modeling Methodologymentioning
confidence: 99%
“…They are particularly appealing for decentralized utilization of intermittent renewable energy as they are capable of both energy generation and storage. However, we found that the switch between endothermic electrolysis mode and exothermic fuel cell mode is particularly challenging for SOC stacks [6] due to the significant spatial and temporal gradients that manifest because of the mode switch (see Fig. 4).…”
Section: Modeling the Transients And Performance Of Reversible Solid ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of mass transport in a thick electrode has been analyzed by [43] in a two-dimensional study that couples mass and heat transport and included methane/steam reforming by means of a catalytic chemical reaction. Basically, in three-dimensional analysis, the governing equations for conservation of mass, momentum, species, thermal energy, electric charge, and electrochemical kinetics in anode and cathode of a SOFC are the same as those of a PEMFC, except that water transport through the electrolyte is not considered [44]. Orthogonal meshes are typically used in modeling planar SOFCs.…”
Section: Solid Oxide Fuel Cellsmentioning
confidence: 99%